Puerarin Restores Autophagosome-Lysosome Fusion to Alleviate Cadmium-Induced Autophagy Blockade via Restoring the Expression of Rab7 in Hepatocytes - Wang, Tao; Wang, Li; Zhang, Yi; Sun, Jian; Xie, Yilin; Yuan, Yan; Gu, Jianhong; Bian, Jianchun; Liu, Zongping; Zou, Hui (Frontiers in Pharmacology, 2021)
Autophagic dysfunction is one of the main mechanisms by which the environmental pollutant cadmium (Cd) induces cell injury. Puerarin (Pue, a monomeric Chinese herbal medicine extract) has been reported to alleviate Cd-induced cell injury by regulating autophagy pathways; however, its detailed mechanisms are unclear. In the present study, to investigate the detailed mechanisms by which Pue targets autophagy to alleviate Cd hepatotoxicity, alpha mouse liver 12 (AML12) cells were used to construct a model of Cd-induced hepatocyte injury in vitro. First, the protective effect of Pue on Cd-induced cell injury was confirmed by changes in cell proliferation, cell morphology, and cell ultrastructure. Next, we found that Pue activated autophagy and mitigated Cd-induced autophagy blockade. In this process, the lysosome was further activated and the lysosomal degradation capacity was strengthened. We also found that Pue restored the autophagosome-lysosome fusion and the expression of Rab7 in Cd-exposed hepatocytes. However, the fusion of autophagosomes with lysosomes and autophagic flux were inhibited after knocking down Rab7, and were further inhibited after combined treatment with Cd. In addition, after knocking down Rab7, the protect effects of Pue on restoring autophagosome-lysosome fusion and alleviating autophagy blockade in Cd-exposed cells were inhibited. In conclusion, Pue-mediated alleviated Cd-induced hepatocyte injury was related to the activation of autophagy and the alleviation of autophagy blockade. Pue also restored the fusion of autophagosomes and lysosomes by restoring the protein expression of Rab7, thereby alleviating Cd-induced autophagy blockade in hepatocytes.